PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PEMBELAJARAN IPS DI MADRASAH IBTIDAIYAH - Susilawati, Samsul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
IPS Integrated Learning is essentially a human activity of daily life, shaped by the social environment and the growing of a civilization. Truth IPS Integrated formed explicitly by the